Dedicated service improves the accuracy of Barrett's oesophagus surveillance: a prospective comparative cohort study. Issue 2 (5th September 2018) - Britton, James; Chatten, Kelly; Riley, Tom; Keld, Richard R; Hamdy, Shaheen; McLaughlin, John; Ang, Yeng
Abstract : Objectives: Standards for Barrett's oesophagus (BO) surveillance in the UK are outlined in the British Society of Gastroenterology (BSG) guidelines. This study aimed to assess the quality of current surveillance delivery compared with a dedicated service. Design: All patients undergoing BO surveillance between January 2016 and July 2017 at a single National Health Service district general hospital were included. Patients had their endoscopy routed to a dedicated BO endoscopy list or a generic service list. Prospective data were analysed against the BSG guidelines and also compared with each patient's prior surveillance endoscopy. Results: 361 patients were scheduled for surveillance of which 217 attended the dedicated list, 78 attended the non-dedicated list and 66 did not have their endoscopy. The dedicated list adhered more closely to the BSG guidelines when compared with the non-dedicated and prior endoscopy, respectively; Prague classification (100% vs 87.3% vs 82.5%, p<0.0001), hiatus hernia delineation (100% vs 64.8% vs 63.3%, p<0.0001), location and number of biopsies recorded (99.5% vs 5.6% vs 6.9%, p<0.0001), Seattle protocol adherence (72% vs 42% vs 50%, p<0.0001) and surveillance interval adherence (dedicated 100% vs prior endoscopy 75%, p<0.0001). Histology results from the dedicated and non-dedicated list cohorts revealed similar rates of intestinal metaplasia (79.8% vs 73.1%, p=0.12) and dysplasia/oesophageal adenocarcinoma (4.3% vs 2.6%, p=0.41). Conclusions: The post-BSG guideline era of BO surveillance remains suboptimal in this UK hospital setting. A dedicated service appears to improve the accuracy and consistency of surveillance care, although the clinical significance of this remains to be determined.